Strategi Peningkatan Kapasitas Aparatur Sipil Negara Dalam Upaya Pelayanan Publik: Studi di Kapanewon Gamping, Kabupaten Sleman, DIY - Subekti Handayani (CV. Ulil Albab Corp, 2024)
Governability shows the extent to which the government can carry out its functions in terms of regulations and public services. The capacity of regional government public services is then important to analyze, especially in relation to its strategy. This research aims to examine the capacity building strategy in public services carried out by Kapanewon Gamping, Sleman Regency. The method used is descriptive qualitative with data collection using interviews, observation and documentation. The informants in this research involved five Kapenwonan Gamping employees and ten community leaders. The research results show that the implementation of strategy at Kapanewon Gamping has been influenced by internal factors in the form of Panewu's leadership, organizational capacity, Kapanewon's internal agreement, space for freedom through delegation of control from Panewu, bona fides from alternative financial sources, and developments in service technology. Apart from that, external factors that influence are political agendas and public support. Specifically relating to organizational capabilities, Kapanewon Gamping has demonstrated regulatory capacity, extractive capacity, distributive capacity, responsive capacity and networking and cooperation capacity.